Electricity generation in dry methane by a durable ceramic fuel cell with high-performing and coking-resistant layered perovskite anode. (1st January 2019) - Ding, Hanping; Zhou, Desheng; Liu, Shun; Wu, Wei; Yang, Yating; Yang, Yingchao; Tao, Zetian
Highlights: A double perovskite PBFN is synthesized and characterized. The nature of mixed electronic and ionic conductor benefits catalysis. High power densities are achieved at 800 °C in H2 and CH4. The anode exhibits stable performance in dry methane. The anode shows strong redox stability. Abstract: A novel A-site deficient ceramic oxide (PrBa)0.95 (Fe0.9 Nb0.1 )2 O5+δ with layered perovskite structure has been investigated as an anode material for a direct-hydrocarbon fueled solid oxide fuel cell. Promising performance of this anode is achieved by stabilizing the material with Nb doping at B sites, which shows excellent chemical stability and high catalytic activity in the reducing fuel condition. The button cell based on lanthanum gallate electrolyte exhibits peak power density of 1.05 W cm −2 in H2, 0.64 W cm −2 in CH4 (∼3% H2 O) and 0.57 W cm −2 in dry CH4 at 800 °C, respectively. When the temperature is decreased to as low as 600 °C, the cell still reaches 0.18 W cm −2 in hydrogen. The anode is highly resistant against redox cycling with capability of rapid recovery from oxidizing condition. Based on a series of performance durability tests under various fuel conditions, this anode material has been demonstrated to be feasible for long-term operation in dry CH4 without observable degradation. The results demonstrate a new technical route to develop highly active and stable ceramic anode by doping high-valence rare-earth elements into B sites of perovskite material.